Resolution of antibiotic mixtures in serum samples by high-voltage electrophoresis. Issue 6 (June 1975) - Reeves, D S; Holt, H A
Abstract : The use of high-voltage electrophoresis and bioautography for the separation mixtures of antibiotics received in clinical serum samples is described. The electrophoretic characteristics of 39 antibiotics are given as is the accuracy of the method for quantitating three antibiotics. In screening 189 consecutive serum samples submitted for routine antibiotic assay, undisclosed antibiotics were revealed by the technique in 35.